2017
DOI: 10.18632/oncotarget.23222
|View full text |Cite
|
Sign up to set email alerts
|

More severe toxicity of genetic polymorphisms on MTHFR activity in osteosarcoma patients treated with high-dose methotrexate

Abstract: 5,10-Methylenetrahydrofolate reductase (MTHFR), a key enzyme for folate metabolism, catalyses the irreversible conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, which is located at the end of the short arm (1p36.3). Two common non-synonymous variants, the C677T (Ala222Val) and A1298C (Glu429Ala), were mainly described with decreased enzymatic activity and an alteration of intracellular folate distribution. Osteosarcomas are currently treated with high dose of methotrexate (MTX). The dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…39 Similarly, Xie et al suggested that genetic polymorphism of MTHFR C677T in the MTX metabolic pathway had no obvious effect on progression-free survival and tumor necrosis rate in sarcoma (age range, 5-52 years). 40 For hematological malignancy, early studies on childhood ALL have reported controversial results. [16][17][18] However, a recent review concluded that there was no association or opposite effects in the majority of published data, and that these two polymorphisms are not suitable predictors of outcome in pediatric ALL.…”
Section: Discussionmentioning
confidence: 99%
“…39 Similarly, Xie et al suggested that genetic polymorphism of MTHFR C677T in the MTX metabolic pathway had no obvious effect on progression-free survival and tumor necrosis rate in sarcoma (age range, 5-52 years). 40 For hematological malignancy, early studies on childhood ALL have reported controversial results. [16][17][18] However, a recent review concluded that there was no association or opposite effects in the majority of published data, and that these two polymorphisms are not suitable predictors of outcome in pediatric ALL.…”
Section: Discussionmentioning
confidence: 99%
“…One study carried out in patients after high-dose MTX-therapy found a significant association between the T allele and liver toxicity in 49 patients with HGOS [ 111 ]. This association, however, was not confirmed in the subsequent meta-analysis, including seven studies with a total of 1044 patients (148 with HGOS), whereas a recent study on 59 Han Chinese patients with HGOS found the variant T allele of MTHFR rs1801133 being associated with higher degrees of liver toxicity [ 108 ].…”
Section: Gene Polymorphisms Associated With Toxicitiesmentioning
confidence: 99%
“…The TT genotype was significantly associated with grade 3–4 hematologic toxicity in 96 pediatric HGOS patients [ 107 ]. In a recent study, the variant T allele of this polymorphism was reported to correlate with higher degrees of hematologic toxicities in 59 Han Chinese patients with HGOS [ 108 ].…”
Section: Gene Polymorphisms Associated With Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among genes related to methotrexate metabolism, the most widely studied in HGOS has been the 5,10-methylenetetrahydrofolate reductase (MTHFR) [15,18]. The most remarkable information on the possible clinical impact about this gene consisted with the association of the variant allele (T) of MTHFR rs1801133 with higher degrees of liver and hematologic toxicities in a series of 59 Han Chinese HGOS patients [19].…”
Section: Candidate Predictive and Prognostic Biomarkersmentioning
confidence: 99%